An Inside Perspective on Magma Intrusion: Quantifying 3D Displacement and Strain in Laboratory Experiments by Dynamic X-Ray Computed Tomography - Poppe, Sam; Holohan, Eoghan P.; Galland, Olivier; Buls, Nico; Van Gompel, Gert; Keelson, Benyameen; Tournigand, Pierre-Yves; Brancart, Joost; Hollis, Dave; Nila, Alex; Kervyn, Matthieu (Frontiers in Earth Science, 2019)
Magma intrusions grow to their final geometries by deforming the Earth’s crust internally and by displacing the Earth’s surface. Interpreting the related displacements in terms of intrusion geometry is key to forecasting a volcanic eruption. While scaled laboratory models enable us to study the relationships between surface displacement and intrusion geometry, past approaches entailed limitations regarding imaging of the laboratory model interior or simplicity of the simulated crustal rheology. Here we apply cutting-edge medical wide beam X-ray Computed Tomography (CT) to quantify in 4D the deformation induced in laboratory models by an intrusion of a magma analogue (golden syrup) into a rheologically-complex granular host rock analogue (sand and plaster). We extract the surface deformation and we quantify the strain field of the entire experimental volume in 3D over time by using Digital Volume Correlation (DVC). By varying the strength and height of the host material, and intrusion velocity, we observe how intrusions of contrasting geometries– cryptodomes, cup shapes, cone sheets and dikes – grow, and induce contrasting strain field characteristics and surface deformation in 4D. We observe dominantly mixed-mode (opening and shear) fracture localisation in low-cohesion material overburden versus opening-mode fracture localisation in high-cohesion material overburden. The results demonstrate how the combination of CT and DVC can greatly enhance the utility of optically non-transparent crustal rock analogues in obtaining insights into shallow crustal deformation processes. This unprecedented perspective on the spatio-temporal interaction of intrusion growth coupled with host rock deformation provides a conceptual framework that can be tested by geological field observations at eroded volcanic systems and by the ever increasing spatial and temporal resolution of geodetic data at active volcanoes.